Expression and purification of SARS-CoV-2 receptor binding domain in Escherichia coli for diagnostic and therapeutic purposes - Hajarossadat Ghaderi; Alireza Shoari; Shima Salehi; Ayda Hassanzadeh Eskafi; Mahdi Habibi-Anbouhi; Reza Ahangari Cohan; Reza Moazzami; Mahdi Behdani (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: SARS-CoV-2 causes a severe respiratory disease known as COVID-19 and is responsible for a global viral pandemic. The SARS-CoV-2 receptor binding domain (RBD) is located on the spike protein, which identifies and binds to the angiotensin-converting enzyme 2 (ACE2) receptor. The RBD is an important target for developing virus-neutralizing antibodies, vaccines, and inhibitors. Experimental approach: In this study, recombinant SARS-CoV-2 RBD was expressed in E. coli BL21 (DE3) and purified and its binding activity was determined. Purification was conducted using the Ni-NTA column. ELISA. flow cytometry assays were set to evaluate the binding ability of recombinant RBD to different anti-RBD antibodies and native ACE2 receptors on HEK293A cells, respectively. Findings/Results: The SDS-PAGE analysis revealed the corresponding band at 27 kDa in the culture after induction with 0.7 mM IPTG, while the corresponding band was not observed in the culture without IPTG induction. ELISA results showed that antibodies produced in the human sera could bind to the recombinant RBD protein and the commercial anti-RBD antibody. Also, flow cytometry analysis revealed that the recombinant RBD could bind to human ACE2 on the surface of HEK293A cells. Conclusion and implication: Our outcomes displayed that the recombinant RBD expressed in the E. coli strain has biological activity and can be used as an antigen for the development of diagnosis kits and vaccines as well as a tool for screening drugs against SASR-CoV-2.